2004
DOI: 10.1074/jbc.m400005200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Mechanism of Store-operated Ca2+ Channels by Zinc

Abstract: Capacitative calcium influx plays an important role in shaping the Ca 2؉ response of various tissues and cell types. Inhibition by heavy metals is a hallmark of storeoperated calcium channel (SOCC) activity. Paradoxically, although zinc is the only potentially physiological relevant ion, it is the least investigated in terms of inhibitory mechanism. In the present study, we characterize the inhibitory mechanism of the SOCC by Zn 2؉ in the human salivary cell line, HSY, and rat salivary submandibular ducts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Furthermore, the membrane is believed to be impermeable to polyvalent anions such as sulphate, citrate and phosphate, based on the fact that the vesicles are stable in 1 mol l -1 solutions of these anions. The same study also revealed that zinc ions at concentrations from 25 to 50 mmol l -1 inhibited rupture (Luchtel et al, 1991), which suggests that calcium channels may be important for the rupture of mucin vesicles, as zinc is known to inhibit some calcium channels (Büsellberg et al, 1991;Gore et al, 2004). Furosemide, a Na…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, the membrane is believed to be impermeable to polyvalent anions such as sulphate, citrate and phosphate, based on the fact that the vesicles are stable in 1 mol l -1 solutions of these anions. The same study also revealed that zinc ions at concentrations from 25 to 50 mmol l -1 inhibited rupture (Luchtel et al, 1991), which suggests that calcium channels may be important for the rupture of mucin vesicles, as zinc is known to inhibit some calcium channels (Büsellberg et al, 1991;Gore et al, 2004). Furosemide, a Na…”
Section: Introductionmentioning
confidence: 90%
“…Store operated calcium channels in the plasma membranes of salivary cells are inhibited by extracellular zinc binding at a site distinct from the channel [106]. In airway epithelial cells exposure to extracellular zinc causes an increase in [Ca 2+ ] cyt by its interaction with the P2X receptor channel [107].…”
Section: Zincmentioning
confidence: 99%
“…A functional link has been proposed between L-type calcium channels and the zinc efflux transporter ZnT1 (Ohana et al, 2006;Segal et al, 2004), and extracellular zinc can trigger the release of calcium from intracellular pools in HT29 cells (Hershfinkel et al, 2001) and inhibit calcium influx in several cultured cell lines (Gore et al, 2004). A dramatic increase in calcium occurs in embryos from zinc-deficient Zip2-knockout mice (Peters et al, 2007).…”
Section: Essential Metal Interactionsmentioning
confidence: 98%